Housing Criteria/Location Selection Using Analytic Hierarchy Process : A Universiti Utara Malaysia Study - Aida Mauziah, Benjamin (2002)

(untitled)
The report presents the findings of a survey of the housing location selection preferences among the Malaysian house buyers, in particular the Universiti Utara Malaysia (UUM) staff. In this study, eight criteria for housing location selection decision were determined and five housing locations were identified. The decision problem was structured into a three level hierarchy using Analytic Hierarchy Process (AHP) technique. The findings revealed that the most important criteria considered by UUM staff in selecting their housing location was road facilities, followed by religious centres and cost of living. Three factors namely, gender, marital status and incomes that might affect one's decision when selecting a housing location were also discussed in this study. Generally, those who were married with family consider road facilities as the most important criteria whereas bachelor house buyers tend to give priority to cost of living. This criterion was also the most important for the first incomes group (RM5000 or less) while social standing of an area was the top criteria for the second incomes group (above RM5000). However, the gender factor did not give much influence for the UUM staff in selecting their housing location. Both the male and female staff considered road facilities the most important criteria. The results of this study may be useful to housing - developers because it provides information regarding the importance of location selection criteria and thus may help housing developers to choose the best housing location to match the house buyers' needs. The AHP model also offers house buyers a systematic framework for making a multiple criteria decision that involves huge investment such as buying a house.